HUBUNGAN KEBIJAKAN DAN KINERJA APARAT DESA TERHADAP KESEJAHTERAAN MASYARAKAT DESA BULO TIMORENG - Anjas Asmara; Monalisa Ibrahim; Kamaruddin Sellang (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
This study aims to determine the relationship between policy and performance of village officials on the welfare of the community in Bulo Timorang Village, Panca Rijang District, Sidenreng Rappang Regency. The population of this study was 128 people (families of recipients of direct cash assistance) while the number of samples was 56 people (families of beneficiaries of BLT assistance). Data collection techniques used in this study were observation, interviews, literature study and questionnaires. The data analysis technique used was validity test, data reliability test, frequency tabulation analysis, and multiple linear regression and hypothesis testing and coefficient of determination analysis with the help of SPSS version 16 application. The results showed that the policy relationship. The results showed that the policy relationship (X1) obtained a tcount value greater than ttable (2,938> 2,006) then H0 is rejected and H1 is accepted. So that the hypothesis which reads the relationship of policy to the welfare of society is partially accepted. The Independent Variable of Village Apparatus Performance (X2) obtained that the tcount value is smaller than ttable (0.821 < 2.006), so H0 is accepted and H2 is rejected. So that the hypothesis which reads that the performance of village officials on community welfare is partially rejected means that there is no effect of X2 on Y. The results of the F test show that the value of Fcount > Ftable or 6.403> 3.17. And a significant level of 0.003 < 0.05, then H0 is rejected and H3 is accepted, meaning that the independent variable (policy relationship (X1) and the performance of village officials (X2) simultaneously or simultaneously affects the dependent variable (community welfare) positively and significantly. the coefficient of determination (R²) shows Adjusted R Square 0.164 or 16.4%, which means that the variation of the community welfare variable can be explained by the policy relationship variable (X1) and the performance of the village apparatus (X2), the remaining 83.6% can be explained by other variables outside the study.